Complexo de paládio com iminas derivadas de diaminas aromáticas: síntese, investigação estrutural, estudo térmico e atividade antineoplásica. - Sarto, Luís Eduardo (2020)
This work presents the synthesis of new palladium (II) compounds from three Schiff bases, N,N-metfen-sOH (L 1 ), N,N-etfen-sOH (L 2 ) and N,N-etdiben (L 3 ). The reaction of these ligands with the palladium precursors, [Pd(AcO) 2 ] e Li 2 [PdCl 4 ] formed three new compounds: [Pd(N,N-metfen-sO) 2 ] (C 1 ), [Pd(N,N-etfen-sO) 2 ] (C 2 ) and [Pd(- AcO)( N,N-etdiben)] 2 (C 3 a). The substitution of complex C 3 a acetates by chlorides, bromides, azides and thiocyanates, and the reaction of this same complex with triphenylphosphine formed others five new complexes. All synthesized compounds, including Schiff bases, were previously characterized by infrared spectroscopy (IR), nuclear magnetic resonance (NMR), CHN elemental analysis, simultaneous thermogravimetry and differential thermal analysis (TGA-DTA) and single crystal X- ray diffraction. Single crystals of compounds C 1 and C 2 were obtained, and the resolution of these structures was very important for the structural elucidation of these compounds. From the X-ray data, the Hirshfeld surfaces were also obtained, complementing the supramolecular characterization of these complexes. The infrared and NMR spectra agree with the proposed structures, indicating the coordination mode of singular synthesized complex. Elemental analysis agrees with the proposed structures. The residual mass of the thermogravimetry analysis agree with the proposed palladium content on structures. The thermal analysis was also used to compare the thermal stability of compounds after substitution reactions. DFT calculations were important for understanding some properties of these complexes, in addition to corroborating the proposed coordination modes. Preliminary experiments to determine the cytotoxic potential of the compounds were carried out against MCF-7 (human breast adenocarcinoma), HepG2 (human liver adenocarcinoma) and A549 (human lung epithelial adenocarcinoma) and showed that three of the new synthesized compounds cause a small decrease in cell viability of this tumor cell line, mainly MCF-7.